Surges of Development and Techno-Economic Paradigms. A Review Essay of the Festschrift for Carlota Perez. - Walter Scherrer (Central European Public Administration Review)
REVIEW OF Techno-Economic Paradigms. Essays in Honour of Carlota Perez, edited by Wolfgang Drechsler, Rainer Kattel and Erik S. Reinert. London and New York 2009, Anthem Press, ISBN-13: 978 1 84331 785 2.